A STUDY TO ASSESS THE EFFECTIVENESS OF MUSIC THERAPY ON HYPERTENSION AMONG NEUROLOGICAL PATIENTS IN SELECTED HOSPITALS OF GUWAHATI, ASSAM - Chapagain, Manju; Borgohain, Unmona; Barman, Ms Mitali (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2017)
Hypertension is one of the most common worldwide diseases afflicting humans and is a majorrisk factor for neurological diseases such as stroke. Due to the associated morbidity andmortality and cost to society, preventing and treating hypertension is an important public healthchallenge.Purpose of this study to investigate the effectiveness of music therapy on hypertension amongneurological patients in selected hospitals of Guwahati, Assam. Methods and materials:A pre– test post test control group design was used in this study to accomplish the objectives.Purposive sampling technique was used for obtaining the adequate sample for the study. Studywas undertaken on 30 neurological patients with hypertension aged ≤30 – ≥ 51 years of selectedhospitals of Guwahati. Results : The mean of pre test blood pressure score of control andexperimental were 144.8 and 153.1. The mean of post test blood pressure score of control andexperimental were 139.7 and 139 respectively. The music therapy was proved effective astested by difference between mean “t” test at 0.01 level of significance as the calculated valueof “t” was 12.62 which greater then tabulated value (2.46) so, was highly significant at 0.01 %level. Conclusion Music therapy is effective in reduction of blood pressure of neurologicalpatients with hypertension. Music therapy can be used as a cost effective non pharmacologicmeasure for blood pressure reduction in order to reduce the burden of hypertension inneurological patients.